Carbon-based composites for removal of pharmaceutical components from water - Bahadorikhalili, Saeed; Sharifianjazi, Fariborz; Azimpour, Maryam; Min Bashi, Neda; Abuchenari, Aliasghar; Borzouyan Dastjerdi, Mahsa; Hashemian, Zahra; Bathaei, Masoud Soroush; Fatemi, Mahnoosh; Hojjati, Mahsa; Esmaeilkhanian, Amirhossein; Ahmadi, Elahe (Journal of Composites and Compounds, 2022)
Carbon-based materials. including carbon nanotubes, graphene, and activated carbon, are among the most effective materials for pharmaceutical components removal from water. Despite the severe effect of pharmaceutical micropollutants in the aquatic environments and the effectiveness of carbon-based composites for water treatment, only a few studies has reviewed carbon-based materials for the removal of pharmaceutical components. Carbon-based materials with special properties like tunable surface functions, abundant pore structure, and high specific surface are used in different water treatment mechanisms such as adsorption and advanced oxidation processes. Graphene, activated carbon, and carbon nanotubes have been widely studied for pharmaceutical components removal. Herein, we have introduced carbon-based materials and reviewed recent studies on their properties, application in water treatment, and possible mechanism for removal of pharmaceutical components from aquatic environments.